Problems and Prospects of Mobile Technologies in the Digital Space of Scientific Knowledge in Libraries - A. Yu. Gerasimenko (Библиосфера)
Mobile transformation is considered as a promising direction for the development of the scientific infosphere. The aim of the study was to determine the prospects for the use of mobile technologies in the digital space of scientific knowledge and to identify the main challenges of their implementation. The research was based on the experience of libraries as the most active participants in the formation of the scientific infosphere and intermediaries in scientific communication. The article describes the practice of libraries on development ready-made mobile platforms (social networks, messengers), creating of own information resources and services with a mobile interface. It reveals possibilities of push-technologies, augmented reality technologies and QR-coding application. The challenges of the introduction of mobile technologies are identified. They are: financial constraints, inefficiency of the IT infrastructure, violation of the privacy and leakage of personal data, lack of qualified personnel, apathy of users. On the basis of the obtained data, prospects of application of mobile technologies in the digital space of scientific knowledge in libraries are disclosed. The first steps to solve the described problems are proposed.